Social Wellbeing by Design for Urban Ageing: Health Awareness and IT Services - Wan Mohd Isa, Wan Abdul Rahim; Hakim Suhaimi, Ahmad Iqbal; Noordin, Nurulhuda; Maisarah Sanusi, Nur Alya; Hanani Azman, Anis; Taufiq Abdul Hajis, Muhd. Shahmi; Damia Mustafa, Nur Batrisyia; Jeffrey Lungin, Vellarie Jun (International Journal of Academic Research in Progressive Education and Development, 2023)
Healthcare is an essential component for sustaining life quality as it advances. The adage "health is wealth" emphasizes that healthcare should be accessible to everyone, regardless of race, age, religion, or socioeconomic status. Although the healthcare sector has significantly expanded and improved over the years, it has shifted focus from societal benefit to commercialization, disproportionately affecting the poor and elderly. The Sustainable Development Goals (SDGs) aim to reduce poverty in all its forms by 2030, and addressing healthcare accessibility is an integral part of this objective. Elderly individuals, particularly those over 60 years old, face challenges due to mobility and potential financial constraints. This paper employs Soft Systems Methodology (SSM) to elucidate the relationship between these issues and enhance stakeholder understanding at a local housing area in Petaling Jaya, Selangor, Malaysia as the case study. With smartphones being ubiquitous in urban areas and the COVID-19 pandemic underscoring the need for accessible healthcare applications, mobile technology offers immense potential for expanding healthcare services in developing countries through remote consultations. This study aims to facilitate easy access to healthcare services for the elderly in urban settings by promoting technological literacy while addressing mobility and cost concerns.